Treats containing cannabidiol, L-tryptophan and α-casozepine have a mild stress-reducing effect in dogs - Flint, Hannah E.; Weller, Jennifer E.; Hunt, Alysia B. G.; King, Tammie (Frontiers in Veterinary Science, 2025)
IntroductionDemand for stress-reducing products aimed at pets has risen in recent years, demonstrated by an ever-growing market of nutritional and odor-based products. Previous research has demonstrated an effect of Cannabidiol (CBD), L-tryptophan and α-casozepine on stress-related behaviours in a variety of animal species, including dogs. The objective of this study was to explore the efficacy of a treat product containing two different doses of CBD (2 mg/kg BW and 4 mg/kg BW) in addition to a 2mg/kg BW dose of CBD combined with L-Tryptophan and α-casozepine (blend) in comparison to a placebo.MethodsA blinded cross-over study was performed in which 54 dogs received a single dose of each treatment two hours prior to exposure to a previously developed stress paradigm (10 min. car travel). A range of behavioural and physiological measures were collected pre/post (plasma CBD levels, serum cortisol) or during (heart rate, heart rate variability, surface temperature, activity, posture, stress-related behaviours, qualitative ratings) the stress paradigm.ResultsAll treatments resulted in elevated post-test CBD levels in the plasma in comparison to placebo (p < 0.001), the 4 mg/kg BW CBD had higher post-test CBD levels in comparison to the 2 mg/kg BW CBD without the blend (p = 0.002). Furthermore, the 2 mg/kg BW CBD combined with the blend treatment resulted in a significantly smaller increase in cortisol from baseline to post-stress (p = 0.016) in response to car travel in comparison to the placebo. However, no other significant effects of treatment were observed, and CBD plasma levels were highly variable between individual dogs, which may have impacted results.DiscussionCBD combined with the blend had a mild stress-reducing effect in dogs. Further exploration of the efficacy of CBD in reducing stress and anxiety, including interactions with different active ingredients and individual differences in absorption and metabolism are warranted.